Pelatihan Otomatisasi Gambar dengan Artificial Intelligence (AI) untuk Ilustrasi pada siswa SMK - Rino Subekti; Johan Bastari; Waskita Cahya; Devi Puspita Sari; Zulhamdani (Yayasan Sagita Akademia Maju, 2026)
The rapid development of digital technology in the creative industry requires vocational high school students to possess competencies that align with current workforce demands. However, the use of digital technology to support illustration creation is still not widely familiar among students. This community service program aimed to enhance students’ knowledge and skills in utilizing image automation technology to create digital illustrations more effectively and creatively. The activity was conducted on May 22, 2026, at SMK Citra Insan Mandiri, Depok involving 32 students. The implementation method consisted of preparation, material presentation, demonstrations, hands-on practice, and evaluation of participants’ work. During the practical session, students created illustrations based on themes of education, environment, and entrepreneurship under the guidance of the service team. The results showed that participants were able to understand the introduced technology and apply it in producing digital illustrations. A total of 28 students (87.5%) successfully completed the assigned tasks independently, while the remaining participants completed them with assistance. In addition to improving technical skills, the program also encouraged creativity and broadened participants’ understanding of the use of digital technology in the creative industry. Therefore, this training provided positive benefits in supporting the development of digital competencies among vocational high school students.